Polyhydroxyalkanoates: Trends and advances toward biotechnological applications - Kalia, Vipin Chandra; Singh Patel, Sanjay Kumar; Shanmugam, Ramasamy; Lee, Jung-Kul (Bioresource technology, 2021)
[Display omitted] •Biowastes as a resource for producing bioplastics such as polyhydroxyalkanoates (PHAs).•Potential PHAs as nontoxic implants, biocontrol, tissue repair, and drug delivery agents.•Strategy for improving soil, delivering biocides, and mulching through PHAs.•Plastic waste management through sustainable technologies. Plastics are an integral part of most of the daily requirements. Indiscriminate usage and disposal have led to the accumulation of massive quantities of waste. Their non-biodegradable nature makes it increasingly difficult to manage and dispose them. To counter this impending disaster, biodegradable polymers, especially polyhydroxy-alkanoates (PHAs), have been envisaged as potential alternatives. Owing to their unique physicochemical characteristics, PHAs are gaining importance for versatile applications in the agricultural and medical sectors. Applications in the medical sector are more promising because of their commercial viability and sustainability. Despite such potential, their production and commercialization are significant challenges. The major limitations are their poor mechanical strength, production in small quantities, costly feed, and lack of facilities for industrial production. This article provides an overview of the contemporary progress in the field, to attract researchers and stakeholders to further exploit these renewable resources to produce biodegradable plastics on a commercial scale.